Impaired endothelial shear stress induces podosome assembly via VEGF up‐regulation. Issue 8 (21st April 2016) - Fey, Theres; Schubert, Kai Michael; Schneider, Holger; Fein, Evelyn; Kleinert, Eike; Pohl, Ulrich; Dendorfer, Andreas
ABSTRACT: Podosomes are dynamic cytoskeletal membrane structures with local adhesive and proteolytic activity. They are critically involved in angiogenesis and vascular adaptive growth. Here, we studied in HUVECs and murine small vessels whether shear stress controls podosome assembly and local proteolytic activity. Podosomes were characterized by immunohistochemistry, and their proteolytic activity was assessed as degradation imprints in fluorescent gelatin that was used as growth substrate. Compared with controls (10 dyn/cm 2 ), the number of podosomes formed per time was doubled when cells were exposed to low shear stress (0.3 dyn/cm 2 ) or even increased 5‐fold under static conditions. This was a result of an enhanced expression of VEGF after reduction of shear stress. Consequently, enhanced podosome formation could be prevented by a VEGF receptor antagonist as well by interruption of VEGF signaling via inhibition of PI3K, Src, or p38. Increase of podosome assembly went along with significantly augmented cell motility. In vivo experiments in mouse arteries confirmed increased endothelial podosome numbers when shear stress was abolished by vessel occlusion. We conclude that shear stress, by reducing VEGF release, inhibits podosome assembly. Hence, endothelial cell‐mediated matrix proteolysis and migratory activity are inhibited, thereby stabilizing the structure of the vessel wall.—Fey, T., Schubert, K. M., Schneider, H., Fein, E., Kleinert, E., Pohl, U., Dendorfer, A. Impaired endothelial shear stress induces podosome assembly via VEGF up‐regulation. FASEB J. 30, 2755‐2766 (2016). www.fasebj.org